Evaluation of pharmaceutical care in Brazilian primary health services settings: expanding objects and approaches - Letícia Santana da Silva Soares; José Antonio Iturri de La Mata; Rafael Santos Santana; Dayani Galato (Universidade de São Paulo, 2022)
Abstract The objective of this work is to reflect on the objects and approaches usually employed in the evaluation of pharmaceutical care and their potential applicability in primary care settings. We conducted the review of the literature, and, to exemplify the advantages of expanding these objects and approaches, a real-world problem situation was selected: morbidity and mortality related to lack of treatment adherence by hypertensive patients in Brazilian primary health care services. Our reflections highlight the need to evaluate the effects of interventions, understood within Donabedian's normative model as 'outcomes,' which can be clinical, humanistic, or economic. Our findings show that most published studies, even those that set out to report outcomes, actually evaluate processes, such as number of visits, number of problems identified, types of problems, or acts of the practice performed by pharmacists. On the other hand, we also identify a need for study designs and indicators to enable 'finer' normative assessment. We also discuss the importance of shifting research toward an evaluative paradigm to allow strategic, logic, effects, production, efficiency, and implementation analyses. Finally, we suggest some possible indicators to evaluate pharmaceutical care interventions in the selected problem situation, through an extension of the objects and approaches proposed.